2010
DOI: 10.1089/fpd.2010.0638
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Foodborne Illness Outbreaks in Qassim, Saudi Arabia, 2006

Abstract: The objectives of this study were to determine the burden of foodborne illness, and to identify the specific foods and causative organisms responsible for foodborne illness outbreaks in Qassim, Saudi Arabia, during the year 2006. The study is a descriptive analysis of the surveillance data for foodborne illness outbreaks, collected by the Preventive Medicine Department, Primary Health Care Administration, Qassim province. We analyzed the foodborne illness surveillance data for the year 2006, using SPSS-11 stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…In another report, in 2011 alone, the 255 incidences for food borne diseases were reported causing illness in 2066 people (Health Ministry Saudi Arabia, 2013). During the year 2006, the main cause of foodborne illness outbreaks in Qassim, a central province of Saudi Arabia, was consuming commercially prepared foods (Al-Goblan & Jahan, 2010). Another incidence of gastroenteritis occurred in Abha city, south-west Saudi Arabia, among customers who had eaten a contaminated ready-made food item (Al-Ahmadi, Elbushra, & Al-Zahrani, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In another report, in 2011 alone, the 255 incidences for food borne diseases were reported causing illness in 2066 people (Health Ministry Saudi Arabia, 2013). During the year 2006, the main cause of foodborne illness outbreaks in Qassim, a central province of Saudi Arabia, was consuming commercially prepared foods (Al-Goblan & Jahan, 2010). Another incidence of gastroenteritis occurred in Abha city, south-west Saudi Arabia, among customers who had eaten a contaminated ready-made food item (Al-Ahmadi, Elbushra, & Al-Zahrani, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the improvement in laboratory capacities in Saudi Arabia reflected an increasing number of food poisoning cases that are attributed to norovirus [43]. In 2006, 31 foodborne illness outbreaks were attributed to Salmonella spp., followed by Staphylococcus aureus and often related to the consumption of Mediterranean meat sandwiches [64]. Salmonella, Staphylococcus aureus, E. coli, Bacillus cereus, and Shigella were major causative agents linked to 16 reported in earlier outbreaks in 2003 [57] and staphylococcus aureus was associated with 41% of bacterial food poisoning cases [65].…”
Section: Surveillance Food Monitoring and Epidemiological Datamentioning
confidence: 99%
“…The study showed that E. coli bacteria formed the highest percentage of intestinal isolates (28.16%). These bacteria are part of the normal flora of the intestine as they are shedding with feces and contaminate the environment therefor, they cause many infections to other birds and humans (7,9,10,16), while E. coli formed (19.44%) isolates from the liver, this bacterium was considered as a serious indicator on the poultry industry as it causes many diseases. The most common Colibacillosis disease as well as Colisepticaemia, Acute airsaculitis and Coligranuloma of liver (17,18,19).…”
Section: -Bacterial Isolationmentioning
confidence: 99%
“…As a result of inappropriate conditions and other reasons due to bacterial infections, opportunistic bacteria were activated and biological processes are affected within the body, intestines and liver are the most affected organs where the liver performs a variety functions in digestive system and the metabolism of proteins, lipid and carbohydrates. Bacteria in chicken intestine play important role in pollution of the environment through mixing of the intestinal content with meat during unhealthy slaughters ,these bacteria are transfer to humans and lead to intestinal infections by toxins which produced (7).The risk of bacterial pathogens represented in two important things: the first concerns with public health, the most cases of intestinal poisoning in humans due to Staphylococcus aureus, E. coli, Salmonella spp and Enterococcus faecalis which is produced intestinal toxins (8,9,10) and other bacterial causes, due to poultry meat consumption (11). The second is the economic importance of poultry diseases, which is a wide world problem, and causes significant economic losses due to a decrease in the rate of fertilization and hatching in flocks, maternal weight loss, reduced egg production and carcass contamination in the slaughterhouse (12).…”
Section: Introductionmentioning
confidence: 99%